Analisis Etika Pemasaran dan Dampaknya terhadap Reputasi Merek pada Kampanye Iklan Air Mineral - Aisyah Humayyrah; Halimah Zahrah; Amelia Rahmadani; Indy Fauziah Hanifa; Nabila Syaharani (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to explore the ethical aspects of Le Minerale's advertising promotion and its impact on brand image. The case highlighted is the Le Minerale billboard showing two unaccompanied babies, which has sparked controversy in society. This research method uses a descriptive qualitative approach by conducting literature studies, observing advertising content, and narrative analysis. The research findings indicate that the advertisement violates the Indonesian Advertising Ethics (EPI) guidelines, especially regarding child exploitation and honesty in delivering messages. This violation causes negative reactions from the public, reduces consumer trust levels, and has the potential to damage brand reputation in the long term. This study emphasizes the importance of integrating ethics in business and consumer protection regulations in marketing strategies, as well as the need for companies to formulate reputation recovery steps through clear and responsible crisis communication. In this context, companies must consider the social and ethical impacts of every marketing decision taken. Therefore, this study can be a reference for companies to increase ethical awareness in product promotion and build a positive brand image in the eyes of consumers. Thus, companies can avoid the same mistakes and increase consumer trust in the brand. In addition, this study can also contribute to the development of marketing ethics and consumer protection theories in Indonesia.